Best Answer

Your answer can be solved by rewriting the equation in point-intercept notation.

* -3x + 2y = 11 * 2y = 3x + 11 * y = (3x+11)/2 That line lists all of the possible answers.

Q: -3x plus 2y equals 11

Write your answer...

Submit

Still have questions?

Continue Learning about Other Math

3x + 2y = 12 ie 2y = 12 - 3x so y = 6 - 3x/2

The equation can be simplified to show a value of Y in terms of X. 3X + 2Y +2 = 4Y + 4 3X + 2 = 2Y + 4 3X -2 = 2Y and 2Y = 3X - 2 means that Y = (3/2 X) -1

If: 3x+2y = 5x+2y = 14 Then: 3x+2y = 14 and 5x+2y =14 Subtract the 1st equation from the 2nd equation: 2x = 0 Therefore by substitution the solutions are: x = 0 and y = 7

3x = 2y + 3 3x -3 = 2y +3 -3 3x - 3 = 2y (3x -3)/2 = 2y / 2 y = 1/2 x (3x - 3) 3x = 2y +3 3x - 3x = -3x +2y +3 0 = -3x +2y +3 -1 x (0) = -1 x (-3x +2y +3) 0 = 3x - 2y -3

3x + 2y = 8 2y=8-3x y=4-1.5x A quadratic has x^2 This is the equation of a line with negative slope.

Related questions

-3x + 2y = 9 2y = 3x + 9y = 1,5x + 4,5

3x + 2y = 7

(2, -1)

3x-2y-7=0

3x+2y=9 2y=9-3x y=-1.5x-4.5

3x = 2y + 7 The standard form is: 3x - 2y - 7 = 0

3x+2y = 1 2y = -3x+1 y = -1.5x+0.5

3x+2y=6 2y=-3x+6 y=-1.5x+3

3x+2y-5=0 3x+2y=5 Im lost im only 12 work out the rest hope i helped

4x-y=2, thereforey=4x-2sub y into 3x+2y=6...3x+8x-4=611x=10x=10/11

3x + 2y = 12 ie 2y = 12 - 3x so y = 6 - 3x/2

The equation can be simplified to show a value of Y in terms of X. 3X + 2Y +2 = 4Y + 4 3X + 2 = 2Y + 4 3X -2 = 2Y and 2Y = 3X - 2 means that Y = (3/2 X) -1